(untitled) (Texas Journal of Engineering and Technology, 2022)
This article introduces the study of urban greening, the use of landscape architecture for contemporary aesthetic and environmental purposes, and highlights the strengths and weaknesses of landscape architecture, landscape analysis, and the development of landscape theory